Kan brugerundersøgelser overhovedet afdække brugernes leksikografiske behov? - Tarp, Sven (LexicoNordica, 2008)
This contribution discusses lexicographic user research on the basis of the function theory. It starts with a theoretical discussion of the concept of lexicographically relevant user needs and points out several different types of lexicographic needs that have to be taken into account when doing user research. It then discusses the positive and negative aspects of the various methods used in lexicographic user research, i.e. questionnaires, interviews, observation, protocols, experiments, tests, and log files. With reference to both lexicographic and sociological literature, it then raises a number of problems common to most of the lexicographic user research carried out until now and calls upon lexicographers to use scientific sociological methods in future research. Finally, it proposes a number of alternative methods in order to get more knowledge about the real user needs.